İŞYERİ HEKİMİ ÇALIŞTIRMA ZORUNLULUĞU - (:unkn) unknown (My University, 2017)
İşyeri hekimi iş sağlığı ve güvenliği alanında görev yapmak üzere Bakanlıkça yetkilendirilmiş işyeri hekimliği belgesine sahip hekimdir. İşyeri hekimi, güvenli bir işyeri ve sağlıklı iş koşullarını sağlamak ve devam ettirmek için işyerindeki iş sağlığı ve güvenliği organizasyonunun kilit elemanlarından biridir. Bu bağlamda Türk hukukunda kanunda düzenlenen koşullarda işyeri hekimi çalıştırmak bir yükümlülüktür.

Occupational physician is a physician who is authorized by the Ministry of Labour and Social Security to work in the field of occupational health and safety and who has occupational medicine certificate. To provide and sustain a safe work place and healthy working conditions, occupational physicians constitute a key element for the occupational health and safety organization of the workplace. Thus, it is an obligation in Turkis.h Law to employ occupational physicians under the conditions regulated by law
OBLIGATION TO EMPLOY OCCUPATIONAL PHYSICIANS
Keywords: Hukuk